2016
DOI: 10.1186/s40673-016-0045-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental neurotransplantation treatment for hereditary cerebellar ataxias

Abstract: Hereditary cerebellar degenerations are a heterogeneous group of diseases often having a detrimental impact on patients’ quality of life. Unfortunately, no sufficiently effective causal therapy is available for human patients at present. There are several therapies that have been shown to affect the pathogenetic process and thereby to delay the progress of the disease in mouse models of cerebellar ataxias. The second experimental therapeutic approach for hereditary cerebellar ataxias is neurotransplantation. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 112 publications
(164 reference statements)
0
5
0
Order By: Relevance
“…Cendelin [52] reported that various types of stem cells can be used for experimental neurotransplantation such as: embryonic or adult neural stem cells, embryonic stem cells, adult stem cells, mesenchymal stem cells isolated from various tissues. In a study of Chen et al [53], HUCBMCs were found to express BDNF and other factors such as NT-3 and GDNF.…”
Section: Discussionmentioning
confidence: 99%
“…Cendelin [52] reported that various types of stem cells can be used for experimental neurotransplantation such as: embryonic or adult neural stem cells, embryonic stem cells, adult stem cells, mesenchymal stem cells isolated from various tissues. In a study of Chen et al [53], HUCBMCs were found to express BDNF and other factors such as NT-3 and GDNF.…”
Section: Discussionmentioning
confidence: 99%
“…Transplantation of distinct types of neural progenitors or stem cells has been broadly tested for replacement of degenerated PCs and/or rescue of functional deficits in several ataxia mouse models (for review, see Cendelin, 2016). Functional benefits were obtained after bilateral transplantation of foetal cerebellar cell suspension directly into the CN of adult pcd (Triarhou et al, 1996) or SCA1…”
Section: Discussionmentioning
confidence: 99%
“…Currently, negligible clinical alleviation of ataxic symptoms has been possible with a combination of physical therapy and drugs. Alternatively, the use of cell replacement therapy has shown notable promise to slow the progression of neuronal degeneration found in multiple neuronal disorders 3 . Cell replacement therapies for these disorders such as traumatic brain injury, Alzheimer’s, Parkinson’s, Huntington’s, amyloid lateral sclerosis, and, of importance to our study, ataxia are currently being investigated 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Cell replacement therapies for these disorders such as traumatic brain injury, Alzheimer’s, Parkinson’s, Huntington’s, amyloid lateral sclerosis, and, of importance to our study, ataxia are currently being investigated 4 , 5 . Within treatments of ataxia, cerebellar Purkinje cells are usually the main target for cell replacement therapy 3 , 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation